Medical help-seeking intentions among patients with early Alzheimer’s disease - Villarejo-Galende, Alberto; García-Arcelay, Elena; Piñol-Ripoll, Gerard; del Olmo-Rodríguez, Antonio; Viñuela, Félix; Boada, Mercè; Franco-Macías, Emilio; Ibañez de la Peña, Almudena; Riverol, Mario; Puig-Pijoan, Albert; Abizanda-Soler, Pedro; Arroyo, Rafael; et al. (Frontiers in Psychiatry, 2023)
Background: Limited information is available on the active process of seeking medical help in patients with Alzheimer's disease (AD) at early stages. The aim of this study was to assess the phenomenon of medical help-seeking in early AD and to identify associated factors.: A multicenter, non-interventional study was conducted including patients of 50-90 years of age with prodromal or mild AD (National Institute on Aging/Alzheimer's Association criteria), a Mini-Mental State Examination (MMSE) score ≥22, and a Clinical Dementia Rating-Global score (CDR-GS) of 0.5-1.0. A multivariate logistic regression analysis was conducted.Results: A total of 149 patients were included. Mean age (SD) was 72.3 (7.0) years, 50.3% were female, and 87.2% had a CDR-GS score of 0.5. Mean disease duration was 1.4 (1.8) years. Ninety-four (63.1%) patients sought medical help, mostly from neurologists. Patients with help-seeking intentions were mostly female (60.6%) with a CDR-GS score of 0.5 (91.5%) and had a greater awareness of diagnosis, poorer quality of life, more depressive symptoms, and a more severe perception of their condition than their counterparts. Lack of help-seeking intentions was associated with male sex (p=0.003), fewer years of education (p=0.005), a low awareness of diagnosis (p=0.005), and a low emotional consequence of the condition (p=0.016).Understanding the phenomenon of active medical help-seeking may facilitate the design of specific strategies to improve the detection of cognitive impairment, especially in patients with a lower level of educational attainment and poor awareness of their condition.